KEKUATAN SPASIAL KLUSTER PERKOTAAN DI KABUPATEN SEMARANG - Abdullah Abdullah; Iwan Priyoga (Jurnal Teknik Indonesia, 2023)
Semarang Regency has 19 sub-districts with diverse regional growth. Several areas have experienced development into urban areas, such as Bawen District, East Ungaran District, West Ungaran District, Bergas District, Pringapus District, and Ambarawa District. Each sub-district has urban areas with different levels of influence. This research aims to identify urban clusters that are formed in the five sub-districts that are the focus of the study and provide an assessment of the urban areas that have the greatest influence. The research method used is quantitative descriptive. Secondary data collection is carried out through documentation techniques, namely by recording and studying statistical data relevant to the problem being discussed. Urban clusters in West Ungaran and East Ungaran Districts reciprocally provide the greatest spatial influence. The spatial interaction between the Bawen and Ambarawa urban clusters is in second place. The smallest spatial flow occurs between urban clusters in Bergas District and East Ungaran District. It is hoped that this research can provide input to the regional government of Semarang Regency to increase social interaction between Bergas District and Ungaran Timur District, through investment activities and development of several areas for industrial activities or other activities that can increase the attractiveness of the two clusters in these two sub-districts